Rituximab in Idiopathic Pulmonary Hemosiderosis in Children: A Novel and Less Toxic Treatment Option - Suzanne W. J. Terheggen-Lagro; Eric G. Haarman; Niels W. Rutjes; J. Merlijn van den Berg; Dieneke Schonenberg-Meinema (MDPI AG, 2022)
Idiopathic pulmonary hemosiderosis (IPH) is a rare, potentially life-threatening chronic disease. Steroids are the cornerstone of treatment, even though toxicity and side-effects are very common. Recently, rituximab (RTX) has been suggested as a treatment option, although evidence for its efficacy and long-term safety is lacking. We describe the disease course of two pediatric patients with IPH that were treated with RTX for over 4 years. Demographics, treatments, and clinical variables such as growth, infections, imaging follow-up by CT, and data from pulmonary function tests were retrospectively described. These are the first two cases described with a long-term follow-up of pediatric IPH patients treated with RTX. RTX was well-tolerated and prevented outbreaks of bleeding. In addition, RTX had a robust steroid-sparing effect resulting in the improvement of growth, pulmonary function, and CT abnormalities.